Diagnostic on logistic system in two provinces (Case study: Savannakhet and Champasack): https://doi.org/10.69692/SUJMRD090135 - SACKBOUAVONG, Khoune; MANIVONG, Khamkeo; XOMVIMANE, Khamphane; SACKBOUAVONG, Sabannga; SYHACHACK, Mithsy (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The study entitled "Analyzing the logistics system of agricultural products ". A case study: Savannakhet and Champasak Provinces. The data used in the study includes both secondary data and primary data obtained from the sample group. The research team conducted a detailed interview with 100 entrepreneurs who are actually involved in agricultural business. The results of the study found that: most of the farmers use six-wheeled vehicles/wheels to transport produce/goods, which numbered 58 units as a percentage, equal to 58% because the farmers used wheeled vehicles which can carry medium to large quantities and are suitable vehicles for carrying goods easily. In terms of the use of cattle-type cargo vehicles, most of them use six-wheeled vehicles/wheels covering 50% and ten-wheeled vehicles covering 50%, chicken transporters covering 78.57% and rice-type transporters covering 72.73%. Regarding the distribution channel of the produce/goods of the farmers, it was found that most of them chose the channel from the farm/garden-local market in the province-wholesaler or chose the channel from the farm/garden-factory-wholesaler-market and the channel from the farm/garden-distribution point accounted for 17%. The results of the test of the factors that affect the management of the logistics management of agricultural products found that the management of the logistics management of small products affects the business up to 76%, which means that the business can have a good opportunity to grow.